PERSEPSI SISWA TENTANG PEMBELAJARAN DARING DI MADRASAH ALIYAH NEGERI KOTA SOLOK - Wulandari .; Afdhal Afdhal (JURNAL BUANA, 2021)
Abstract This research discusses the Students' Perceptions of Online Learning in MAN Kota Solok. The purpose of this study was to describe the students' perceptions about online learning at Madrasah Aliyah Kota Solok. The type of research used in this research is descriptive type with a qualitative approach. The data collection technique in this research is by using observation, interview and documentation. The informants involved in this study were MAN Kota Solok. The results of this study can be seen that students have perceptions in the implementation of online learning for the first time done in schools with no readiness from teachers and students, the ability of teachers in the field of technology is also lacking, in terms of facilities are also limited, in terms of networks there are still many students who are constrained. , students often complain of the large number of assignments compared to face-to-face assignments due to the limited time set during the online learning period. whereas from the positive impact students can communicate easily via the internet at any time without being limited by distance and place. Keywords: online learning, Student perpection, impact